2019
DOI: 10.1111/tpj.14517
|View full text |Cite
|
Sign up to set email alerts
|

Theanine transporters identified in tea plants (Camellia sinensis L.)

Abstract: SummaryTheanine, a unique non‐proteinogenic amino acid, is an important component of tea, as it confers the umami taste and relaxation effect of tea as a beverage. Theanine is primarily synthesized in tea roots and is subsequently transported to young shoots, which are harvested for tea production. Currently, the mechanism for theanine transport in the tea plant remains unknown. Here, by screening a yeast mutant library, followed by functional analyses, we identified the glutamine permease, GNP1 as a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 55 publications
9
107
0
Order By: Relevance
“…It is intriguing that many of the highly expressed AAT genes in roots and shoots are AAP family members. This implies the importance of AAP transporters in the tea plant, as previously identified [ 33 ], as well as in rice [ 44 , 45 ] and Arabidopsis [ 46 , 47 ]. This study showed that CsAAPs have distinct expression patterns, suggesting functional specialization.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…It is intriguing that many of the highly expressed AAT genes in roots and shoots are AAP family members. This implies the importance of AAP transporters in the tea plant, as previously identified [ 33 ], as well as in rice [ 44 , 45 ] and Arabidopsis [ 46 , 47 ]. This study showed that CsAAPs have distinct expression patterns, suggesting functional specialization.…”
Section: Discussionsupporting
confidence: 53%
“…AATs might be involved in the homeostasis of AAs and in their sequestration in organelles; thus, their expression patterns may affect tea taste quality [ 33 , 35 ]. The expression of AATs involved in soil-to-root (uptake) would depend on AA recognition as substrates and AA availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Huang et al reported that supplying tea plants with different forms of N significantly increase Pro, Glu, and Thea in tea leaves compared with 0 N, especially when supplied with NH 4 + -N 58 , whereas they did not examined amino acid contents changes in tea plant root. Actually, previous studies reported that many amino acids are mainly synthesized in tea root, and are then transported from root to shoot 41,44,45 ) treatments for 5 min and 96 h on gene expression, but they mixed root, stem, leaf and shoot samples together for the analysis. Thus, the tissue-specific response of gene expression could not be elucidated 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the gene encoding for theanine hydrolase has not been identified yet. Finally, it is noteworthy that Thea is mainly synthesized in roots and is transported through the vascular system to tea plant shoots [41][42][43][44][45] .…”
mentioning
confidence: 99%